Die Evolution indigener Politik in Bolivien - Rice, Roberta (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
This study examines the emergence of indigenous movements as powerful new social and political actors in Latin America. Bolivia’s indigenous movement, in particular, stands out for its mobilizational and organizational capacity in uniting diverse sectors of civil society in the struggle against neoliberalism. The study explores the evolution of indigenous movement strategies in Bolivia, beginning from the transition to democracy in the early 1980s until the presidential victory of indigenous leader Evo Morales of the Movement Toward Socialism (MAS) party in late 2005. Special attention is paid to the rise of contemporary indigenous-based parties rooted in established social movement organizations as well as the role of the indigenous movement in the Bolivian ‘Water War’ of 2000 and the ‘Gas War’ of 2003. The study contends that the success of Bolivia’s contemporary indigenous movement is largely the result of its two-pronged strategy based on unwavering opposition in both the streets and in parliament and its capacity to combine competing class- and ethnic- based demands.